O ensino da psicologia social comunitária nos cursos de graduação em psicologia nas instituições de educação superior do sul do Brasil: concepções teóricas - Batista, Iracema Dimaria Evangelista (2016)
This dissertation is the result of a survey that aimed to know the current situation of the Community Social Psychology (PSC) discipline in Psychology courses of Higher Education Institutions (HEIs) in Southern Brazil. This research intents to analyze the conceptual and theoretical framework of disciplines PSC and/or similar, in graduation courses in Psychology (HEI) in southern Brazil. For the development of this discussion we address the historical context of the discipline of Social Psychology, the historical context in which Psychology is effective as graduation course in Brazil, its recognition and inclusion of the discipline PSC. The methodology focuses on bibliographical and documentary survey along the analyzed HEIs, being a descriptive research, and divided in two stages. In the first stage were identified the HEI in Southern Brazil that offer graduation courses in Psychology. The second stage dealt with the data collection and analysis , including the following dimensions: curriculum matrices, contents and bibliographies (when available) used in the disciplines. It was found that a small number of HEI offer the discipline. However, although this number is small, it is noted that when the offer takes place, discipline is usually mandatory. There was an overlap of Social Psychology discipline in relation to the discipline PSC and / or similar, both in the size of the contents as bibliographies. This finding suggests little understanding of the specificity of the subject by the educational institutions, which might be prejudicial to the formation of the psychologist regarding the PSC.